Performance of Health Service Employees of Sukoharjo Regency Reviewed from Competence, Integrity, Work Experience and Job Placement - Sri Haryanti; Sudarwati; Istiatin (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Performance of Sukoharjo Regency Health Office Employees Reviewed from Competence, Integrity, Work Experience and Job Placement. This study aims to determine and explain the influence of competence, integrity, work experience and job placement on the performance of Sukoharjo Health Office employees. The population of this study was 112 Sukoharjo Health Office employees and saturated samples. Data collection using questionnaires. Data analysis techniques using the Multiple Linear Analysis method. The results of the study showed that competence, integrity, work experience and job placement had a positive and significant effect by contributing to Performance by 87.5% while the remaining 12.5% was explained by other variables not submitted in this study. Suggestions from this study, Sukoharjo Health Office Employees can improve their competence and integrity along with increasing work experience wherever employees are placed so that they can improve performance in the office.